Evaluation of Root Canal Morphology of Mandibular First and Second Premolars Using Cone Beam Computed Tomography in a Defined Group of Dental Patients in Iran - Neda Hajihassani; Neda Roohi; Karim Madadi; Mahin Bakhshi; Maryam Tofangchiha (Scientifica, 2017)
Background. Successful dental root canal treatments require a complete knowledge of dental anatomy and root canal morphology. Materials and Methods. One hundred and forty-five cone beam computed tomography (CBCT) images were used to assess the anatomy and morphology of mandibular premolars based on Vertucci’s classifications in a defined group of dental patients in Iran. The number of roots and root canals, root canal morphology, root and canal shape (curvature), existence of C-shaped canal, and influence of sex on each of these were evaluated. A chi-squared test was used for statistical analysis. Results. The mandibular first and second premolars had a single root in 95.97% and 100% cases, respectively. In the mandibular first premolars, 62.2% were of type I, 0.8% type II, 10.9% type III, 0.8% type IV, 20.3% type V, 4.2% type VI, and 0.8% type VII; in the second premolars, 78% of canals were of type I, 3% type II, 11% type III, 7% type V, and 1% type VI. C-shaped canals did not exist in either of the premolars. The most prevalent root and canal shape was straight. The most prevalent root curvature was a distal curvature in both premolars (71.4% and 74% of first and second premolars, resp.). The most prevalent canal curvature was lingual and buccal for the first premolars (7.6% each) and distal for the second premolars (11%). No significant difference was found between men and women in nearly all of the above (P>0.05). Conclusion. The results suggest that there is a need to conduct further evaluations on finding root and canal variations among more populations to gain better knowledge prior to root canal treatment.